PENGARUH PEMBIAYAAN MUDHARABAH, MUROBAHAH, DAN MUSYARAKAH TERHADAP PERTUMBUHAN ASET BANK SYARIAH DI INDONESIA - Muhammad Ridwan Hidayat; M. Akmal Arrahman; Muhammad Akmal Abdurrahman (Program Studi Ekonomi Syariah, 2025)
This research endeavors to scrutinize how mudharabah, murabahah, and musyarakah funding influence the increase in assets held by Islamic banks operating in Indonesia, employing the Autoregressive Distributed Lag (ARDL) methodology. Temporal data was dissected utilizing assessments of stationarity, cointegration tests via Bounds Test, alongside short-term and long-term projections. The outcomes reveal a cointegrated connection linking Islamic financial arrangements with the expansion of Islamic banking assets. When considering the immediate future, mudharabah funding notably impacts asset expansion, contrasting with murabahah and musyarakah, which do not exhibit notable effects. Looking at the extended horizon, murabahah funding is shown to have a favorable and substantial effect on the upswing of assets within Islamic banks, whereas both mudharabah and musyarakah indicate a positive yet non-substantial influence. These discoveries substantiate the ongoing prevalence of murabahah as the principal mechanism fueling the advancement of Islamic banks' asset portfolios throughout Indonesia.